Combination of Solid‐Phase Micro‐Extraction and Direct Analysis in Real Time‐Fourier Transform Ion Cyclotron Resonance Mass Spectrometry for Sensitive and Rapid Analysis of 15 Phthalate Plasticizers in Beverages. Issue 2 (9th December 2014) - Wu, Mengxi; Wang, Haoyang; Dong, Guoqing; Musselman, Brian D.; Liu, Charles C.; Guo, Yinlong
Abstract A method for rapid identification and quantification of phthalate plasticizers in beverages was developed. A number of 15 phthalate plasticizers which covered all the phthalates concerned in the US Consumer Product Safety Improvement Act (CPSIA), European Union legislations and Chinese national standards (GB) were analyzed. By a combined solid‐phase micro‐extraction (SPME) and direct analysis in real time mass spectrometry (DART‐MS) approach, phthalates at sub‐ng·mL−1 levels can be qualitatively and quantitatively analyzed in a short time. The use of ultrahigh‐resolving power and the accurate mass measurement capacity naturally provided by Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS) minimizes the matrix interferences and thus enables the evaluation of phthalates in a complex matrix without extensive sample handlings or preparations. The limits of quantification (LOQs) were estimated to be at 0.3–5.0 ng·mL−1, lower than the Maximum Residue Limit (MRL) regulated by the European Union legislations (2007/19/EC) in foods, beverages, food packaging and toys (0.3–30 ng·mL−1). This rapid and easy‐to‐use SPME‐DART‐FT‐ICR‐MS method provided a relatively high‐throughput and powerful analytical approach for quick testing and screening phthalates in beverages and water samples to ensure food safety.